Evaluation of the clinical characteristics and outcomes of patients admitted to intensive care units after the Kahramanmaras (Türkiye) earthquake: a multicenter observational study - Burcin Halacli; Goksel Guven; Esat Kivanc Kaya; Mehmet Yildirim; Nihal Deniz Bulut Yuksel; Gamze Kocak; Kadir Bulut; Derful Gulen; Begum Erdemir Sullu; Banu Kilicaslan; Asir Eren Seven; Emin Gemcioglu; et al. (Frontiers in Medicine, 2025)
IntroductionThe outcomes of patients admitted to intensive care units (ICUs) after earthquakes that occurred on the 6th of February 2023 in Türkiye are unknown. Our objective was to delineate the demographic and clinical characteristics, therapeutic approaches, and ICU outcomes of earthquake victims who were hospitalized in Turkish ICUs.MethodsThis was a retrospective multicenter study of adult patients admitted to 12 ICUs across eight tertiary hospitals located in five different cities within 2 weeks after consecutive earthquakes. Clinical and laboratory data were documented at four specific time intervals: upon hospital admission and during the first, second, and third days of ICU admission. To identify independent predictors of ICU mortality, a binary logistic regression model was used for variables identified from the univariate analysis.ResultsA total of 201 patients were admitted to ICUs. The median age of the entire cohort was 36 [26–54] years. 87 patients were male (43.3%), and 114 were female (56.7%). The majority of patients (79.1%) were initially admitted to the emergency department. The median duration of being trapped under the rubble was 12 [5–31] hours. The primary reason (63.7%) for ICU admission was crush syndrome. Acute kidney injury (AKI) was identified in 61.5% of patients. Of 201 patients, 184 had information regarding ICU survival. The ICU mortality rate was 10%. A five-year increase in age, the presence of crush syndrome, and the requirement for vasopressor therapy during ICU care were independently associated with increased ICU mortality rates, while an increase of one point in the Glasgow Coma Scale (GCS) score was favorable for ICU mortality.ConclusionThis study demonstrated that crush syndrome accounted for 63.7% of the reasons for ICU admissions. The ICU mortality rate was recorded as 10%. Noteworthy independent risk factors for mortality were the presence of crush syndrome, increased age, vasopressor treatment and lower GCS score.